Archaeology and Assemblage. Issue 1 (11th January 2017) - Hamilakis, Yannis; Jones, Andrew Meirion
Abstract : Assemblage is a concept common to a number of academic disciplines, most notably archaeology and art, but also geology and palaeontology. Archaeology can claim a special link to the term assemblage, though novel approaches to the concept of assemblage have recently been adopted from the fields of philosophy and political theory. These approaches, bracketed under the term 'new materialism', are discussed here. The introduction to this collection of papers outlines these approaches and evaluates their usefulness for archaeological practice and interpretation.